Micromorfologia de solos modais do estado de Minas Gerais - Lilian Coeli Leite da Silva (2016)
In order to characterize the macro and micromorphological pedological diversity of Minas Gerais brazilian state, a collection with complete modal profiles and no deformations samples was created by the Solos de Minas Project (FEAM/CETEC/UFOP/UFV/UFLA). The collection consists of 20 profiles. 12 were selected for micromorphological study: ORGANOSSOLO HÁPLICO; VERTISSOLO EBÂNICO; PLINTOSSOLO HÁPLICO; ESPODOSSOLO HUMILÚVICO; ARGISSOLO AMARELO; ARGISSOLO VERMELHO; ARGISSOLO VERMELHO AMARELO; LATOSSOLO AMARELO; LATOSSOLO VERMELHO Acriférrico; LATOSSOLO VERMELHO AMARELO; LATOSSOLO VERMELHO Distrófico; and LATOSSOLO VERMELHO Perférrico. This work aims to relate the micromorphology of the studied soils to pedogenetic processes; to carry out a comparative analysis for the studied soils considering their porous systems, microstructures, relations c/f and the identified pedofeatures; and, finally, to evidence possibilities of interpretations and applications of micromorphology related to the management, genesis and pedogenetic evolution of the soil profiles studied. Considering the soils' low anthropogenic interference, this characterization presents the structuring of these soils on a micro scale, whose interpretation associates features, processes and effects in the macro scale, either in the profile or in the pedological cover. For each sampled soil, undisturbed small blocks were extracted and used for making thin and polished sections. Micromorphological descriptions were performed according to the precepts currently proposed by George Stoops. For the ORGANOSSOLO HÁPLICO, the evolution of a weakly developed fissural microstructure to a moderately developed angular block is noted from the base of the profile towards the top; closed porphyric pattern that becomes open porphyry; and evident increase of pedofeatures of incomplete dense filling from pedofauna activity passage type and soft sub-rounded excrements constituting porous microaggregates. The microstructure evolution is associate to the existence of rounded quartz grains - zones of weakness - and the intense biological activity. For the ESPODOSSOLO HUMILÚVICO, there are incipient alumina-organic coats on apedic material, monic coarse pattern in the A and E horizon and chito-gefuric in the spodic horizons. PLINTOSSOLO HÁPLICO presents microstructure in angular to subangular blocks from moderate to well developed, open porphyric pattern, micromass of kaolinite-gibbsitic or hematite nature, associated to oxy-reduction processes. Pedofeatures derived from processes of migration of clay and varied nodules indicate different phases of oxy-reduction processes, associate to past hydrological conditions different from the current ones. Anortic nodules of ferruginous nature are indicative of colluvial process, indicating probable polygenetic origin for this soil. The VERTISSOLO EBÂNICO has a classic micromorphological configuration. The Latosols presented granular microstructure, independent of the lithology on which they have been developed. The Argisols present the greatest diversity of pedofeatures, indicating greater pedogenetic development among the soils studied. The pore system and the b-fabric evidence an intergrade between two of the studied latosols and the argisols.